Oral Lesion Caused by Improper Removable Partial Denture - Riani Setiadhi; Kosterman Usri (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2018)
Oral lesions are relatively common findings in clinical practice, can occur due to various factors such as trauma, systemic diseases, autoimmune disorders, malignancies. Local trauma as one of the cause of oral lesions majority due to poor dentures, fractured restorations and sharp edges of teeth. The lesions are commonly found on the mucosa that is subjected to the source of trauma such as buccal mucosa, lateral border of the tongue or lips. Removable partial denture is a denture that can be removed and reinserted without professional help. Poor removable denture which is an ill-fitting denture, rough/sharp/overextended flanges, or lack of retention/stability could cause oral lesions. This case report describes a 76 old year man complained of pain on his right lateral tongue since 6 months ago. He was wearing a removable upper right denture which cannot be remove for about a year. It was a rough and sharp self-curing acrylic denture. There was erythematous and pain on his lateral right of the tongue but no induration on palpation. Triamcinolone acetonide 0,1% in orabase was the given treatment for the right lateral of the tongue and referred him to the prosthodontic department for replacing the denture. The oral lesion was healed after one week of treatment and the poor denture was removed. As a conclusion dentures should be made properly by the expert in order to prevent oral lesions.